Modulatorji apoptoze kot nova zdravila - Vidic, Iztok (Farmacevtski vestnik, 2006)
Defects in regulation of apoptosis result in a number of human diseases for which there are no adequate medical or pharmacological treatments. Many drug discovery studies have focused on small molecular modulators of apoptosis-relevant proteins, like caspases, protein kinases, inhibitors of apoptotic proteins (IAP), Bcl-2 family proteins and others. For example, preclinical studies of reversible caspase-3 inhibitor have shown its potential neuroprotective role in animal models of Huntington disease. An irreversible broad spectrum caspase inhibitor for chronic hepatitis C virus infection is in the phase II clinical trials. An inhibitor of tyrosine kinase involved in the regulation of cell proliferation is being used for the treatment of chronic myeloid leukaemia and some gastrointestinal tumours since2001. Modern drug development strategies involve also the use of antisense mRNA in cancer treatment. Among the most successful is the antisensetargeting of BCL-2, which is currently being reviewed for the approval by the European Medicines Agency. The knowledge about the functions of proteins involved in apoptosis and of their modulators is therefore crucialfor designing new drugs, which promote or suppress apoptosis according to the aetiology of disease.
Keywords: Apoptosis; Apoptoza; Beljakovinske kinaze; drug; Drug Effects; Hepatitis C; Huntington's Disease; inhibitorji; Leukemia; Levkemija; Oligonucleotides, Antisense; Oligonukleotidi protismerni; Protein Kinases; zdravila